1997
DOI: 10.2105/ajph.87.5.817
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the race/ethnicity of generalist physicians and their care for underserved populations.

Abstract: OBJECTIVES: The purpose of this study was to examine empirically the relationship between physicians' race or ethnicity and their care for medically underserved populations. METHODS: Generalist physicians who received the MD degree in 1983 or 1984 (n = 1581) were surveyed. The personal and background characteristics of four racial/ethnic groups of physicians were compared with the characteristics of their patients. RESULTS: When the potentially confounding variables of gender, childhood family income, childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 19 publications
4
72
0
1
Order By: Relevance
“…The finding that female black physicians have a much larger proportion of Medicaid patients in their practices is interesting. Although consistent with previous findings that black physicians are more likely than whites to care for the underserved and medically indigent, [15][16][17] in this study, the findings were most pronounced for black women. Our regression analysis confirmed that providing services to a large proportion of patients who are enrolled in Medicaid adversely influence physicians' incomes.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that female black physicians have a much larger proportion of Medicaid patients in their practices is interesting. Although consistent with previous findings that black physicians are more likely than whites to care for the underserved and medically indigent, [15][16][17] in this study, the findings were most pronounced for black women. Our regression analysis confirmed that providing services to a large proportion of patients who are enrolled in Medicaid adversely influence physicians' incomes.…”
Section: Discussionsupporting
confidence: 92%
“…First, recent work shows that several aspects of physician behavior and patient ratings of care vary by physician race and sex. 19,20 Minority physicians, for example, often serve a sicker and more socioeconomically vulnerable patient population [21][22][23][24] and encounter more diffi culties obtaining hospital admissions and referrals for their patients. 25 Would potential concerns about the importance of insurance status affect the referral decisions of black physicians and white physicians differently?…”
Section: Introductionmentioning
confidence: 99%
“…Or cette représentation accrue des minorités au sein des professionnels a également vocation à améliorer l'offre de soins qui leur est accessible. Les professionnels issus des minorités s'installent en effet plus volontiers que les autres dans les quartiers à forte composante minoritaire, quartiers qui sont généralement insuffisamment pourvus (Xu et al, 1997). Or la désertification sanitaire caractérise les quartiers habités par les minorités ethnoraciales mais aussi les quartiers défavorisés d'un point de vue socioéconomique.…”
Section: Les Politiques : Peut-on Cibler Sans Stigmatiser ?unclassified